Knowledge, Behaviors, and Attitudes of Polish Nurses As Compared With Evidence-Based Practice in Relation to the Guidelines of the European Resuscitation Council - Dorota Ozga RN, PhD, MBA, CCRN; Marzena Jędrzejczyk-Cwanek RN, PhD; Krystyna Woźniak Msc, CCRN; Edyta Niemczyk RN, PhD; Wioletta Mędrzycka-Dąbrowska RN, PhD, CCRN (Global Advances in Health and Medicine, 2019)
Background The emphasis on Evidence-Based Practice (EBP) is taking on new importance as the profession of nursing strives to meet the challenge of defining the direction of health care, promoting optimal outcomes, and ensuring patient safety. Therefore, Evidence-Based Practice has never been more important to nursing than in the current health-care environment. Objective The study was designed to assess the knowledge, behaviors, and attitudes of nurses as compared with Evidence-Based Practice in relation to the Guidelines of the European Resuscitation Council. Methods The study covered involved a total of 236 nurses who participated in a cardiopulmonary resuscitation course over a period of 12 months. The nurses who qualified for the study followed a complete study registration procedure. Results The current findings show that the lowest score was achieved in the domain of attitude toward selected Evidence-Based Practice aspects in professional work. Detailed domain questions concerned nurses’ Evidence-Based Practice and its limitations related to procedures, the lack of equipment and personnel issues, as well as the lack of scientific evidence. Furthermore, nurses saw clinical experience as being more valuable than research findings for practical decision-making than research findings, and, according to the respondents, they presented opinions that the best way to assess the effectiveness of an action was through clinical experience. In addition, the nurses gave low scores and tended to underestimate the critical literature review aspect within the domain, along with its significance for the general professional practice, believing that search for scientific evidence alone does not apply into their professional work. Conclusions The validated Polish version of the Evidence-Based Practice profile questionnaire is a reliable instrument. The study demonstrates that nurses are facing a multitude of limitations due to procedures, the lack of equipment, and personnel issues. Currently perceived as very poor, the ability to make critical assessments and synthesize evidence should be improved. According to the nurses, clinical experience cannot be the only and the best way to assess the effectiveness of a given measure.